Pupil's and teachers' views about the nature of science - Ayayee, Ellis Koe (My University, 2016)
Bacon’s ideas have been modified and improved by some and contested by others over the centuries. Logical positivism, which evolved from empiricism, has two important tenets, namely, observation and deductive logic in reasoning. As with empiricism, knowledge is considered as objective and reliable (Chalmers, 1983). [Abbreviated Abstract. Open document to view full version]
A research project submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Science. November 1995.
Keywords: Science--Study and teaching (Secondary)--South Africa; Science--Philosophy